The complete chloroplast genome of Androsace mariae - Yupeng Guo; Rui Ma; Jun Xie; Qiujuan Liu; Ye Zhu; Wenjing Yang; Lina Gao; Yanjun Ma (Mitochondrial DNA. Part B. Resources, 2021)
The complete chloroplast genome of Androsace mariae was sequenced and assembled. It is a circular form genome of 151,958 bp in length, which was separated into four distinct regions, a large single-copy (LSC) of 83,292 bp, a small single-copy region (SSC) of 16,744 bp, two inverted repeats (IR) of 25,961 bp. After annotation, a total of 133 genes were predicted, of which, 87 were encoded proteins, 8 rRNA, and 37 tRNA. The evolutionary history, inferred using the neighbour-joining method, indicates that A. mariae was grouped within Primulaceae, and comprised a clade with other three species in Androsace, Androsace paxiana, Androsace laxa and Androsace bulleyana, with 100% bootstrap value.